Now then : a novel - Radford, Morgan, 1987- (Amistad, an imprint of HarperCollins Publishers, 2026)
"Charmaine Wilkerson's Black Cake meets Past Lives in this sweeping debut about a Harvard student uncovering her mother's secret past of fleeing Cuba during a revolution, while navigating her own path to self-discovery. From an NBC News anchor and Today Show correspondent, Now Then is a powerful debut novel about hidden histories, second chances, and the choices-and loves-that shape our lives"-- Provided by publisher.